Hysteroscopic Resection for Missed Abortion: Feasibility, Operative Technique and Potential Benefit Compared to Curettage - de Codt, Matthieu; Balza, Claire; Jadoul, Pascale; Forget, Patrice; Squifflet, Jean-Luc; Bernard, Pierre; Luyckx, Mathieu (Frontiers in Surgery, 2020)
Objective: To evaluate the feasibility of hysteroscopic resection (HsR) for primary surgical management of missed abortion. Reproductive outcomes and potential benefit of this technique will be compared to traditional dilatation and curettage (D&C). Design: Retrospective cohort study in two Departments (Gynecology and Obstetrics) of a tertiary medical care center (Canadian Task Force classification II-2). Patients: Women with first trimester missed abortion. Intervention: Two techniques were used for the management of missed abortion: ultrasound-guided dilatation and curettage (D&C) and hysteroscopic resection (HsR). Results: We evaluated 358 patients who underwent primary surgical removal of missed abortion. 173 patients have been treated by D&C and 185 underwent HsR. In the HsR group, 110 patients (59.5%) have obtained their pregnancy with in vitro fertilization (IVF) versus 7 patients (4.0%) in the D&C group which make the HsR population hypofertile in comparison to the D&C population. The intra- and post-operative complication rates are low and comparable. Intrauterine anomalies were diagnosed during the HsR in 10 patients (5.4%) and could be investigated after the intervention as a possible cause of miscarriage. Because of the difference in term of fertility, the reproductive outcomes have been analyzed by multivariate analysis. The hazard ratio of pregnancy at 6 months, adjusted to the factor IVF for D&C compared to HsR is 0.69 [0.49-0.96] (p=0.026). That could represent a significant benefit in the particular population followed in IVF, but regarding the retrospective analysis, and the very different population in the 2 groups, it doesn’t allow us to draw any evidence based conclusion. Conclusion: Hysteroscopic resection is a feasible and safe procedure for the management of missed abortion that could increase the diagnosis of uterine abnormalities. With all the limitation of the design of our study, our data seems to show a trend to a potential benefit in term of reproductive outcomes for hypofertile patient undergoing IVF treatment.